A zirconium-based metal organic framework-based photosensitizer immobilized esophageal stent coating and preparation and application thereof

By immobilizing esophageal stent coatings with photosensitizers based on zirconium-based metal-organic frameworks, the problems of easy leakage of photosensitizers and insufficient ROS delivery have been solved, achieving improved stability and therapeutic efficacy, adapting to changes in the tumor microenvironment, and providing more precise tumor treatment.

CN122440910APending Publication Date: 2026-07-24CHANGZHOU TEXTILE GARMENT INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610606639.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-06
Publication Date
2026-07-24

AI Technical Summary

Technical Problem

Existing esophageal stents, when used to treat esophageal cancer, are prone to photosensitizer release, leading to excessive spontaneous release, insufficient ROS transmission time and distance, and inadequate response of the tumor microenvironment, resulting in poor treatment efficacy and increased risk of rupture of the stent covering due to tumor progression.

Method used

An esophageal stent coating based on a zirconium-based metal-organic framework and immobilized with photosensitizers is used. The coating consists of a nitric acid/polyethyleneimine intermediate adhesion layer, a PCN-224 NPs photodynamic layer, and a MnO2 smart response channel layer. The stent generates reactive oxygen species through laser excitation, which adapts to changes in the tumor microenvironment and enhances the therapeutic effect.

Benefits of technology

It achieves stable fixation of photosensitizer, prolongs retention time, improves the killing effect on tumor cells, significantly improves the hypoxic environment of tumors, provides more precise targeted therapy, and reduces the risk of tumor progression and membrane rupture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122440910A_ABST
    Figure CN122440910A_ABST
Patent Text Reader

Abstract

The application provides a zirconium-based metal organic framework-based photosensitizer immobilized esophageal stent coating and preparation and application thereof, and the esophageal stent coating comprises a picenolic acid / polyethylene imine intermediate adhesion layer, a PCN-224 NPs photodynamic layer arranged on the intermediate adhesion layer and a MnO2 intelligent response channel layer arranged on the photodynamic layer and used for in-situ reaction to relieve hypoxia; Zr ions in the PCN-224 NPs photodynamic layer are combined with phenolic hydroxyl groups of the picenolic acid / polyethylene imine intermediate adhesion layer and are fixed on the surface of the TA / PEI adhesion layer. The esophageal stent coating can initiate photochemical reaction under light irradiation, can efficiently and long-term kill tumor cells, and the 4-week retention rate in tumor tissues can reach 90.63%, and the tumor cell killing effect is still 89.50%; meanwhile, the esophageal stent coating has safety and biocompatibility; can act according to tumor microenvironment, such as hypoxic conditions, acidic pH value and endogenous H2O2, has more precise targeting effect; and can be applied to local treatment of malignant esophageal tumors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomedical technology, specifically to a photosensitizer-immobilized esophageal stent coating based on a zirconium-based metal-organic framework, its preparation, and its application. Background Technology

[0002] Esophageal cancer (EC) is the eighth most common malignant tumor worldwide, and it is difficult to cure with a poor prognosis. Currently, chemotherapy is the most common treatment for EC, but while chemotherapy drugs kill tumor cells, they also cause systemic toxicity. Furthermore, they are unlikely to relieve symptoms such as difficulty swallowing caused by esophageal stricture resulting from cancer.

[0003] Esophageal stenting, as a recommended palliative treatment in clinical practice, can directly target the area of ​​malignant stricture, support the narrowed lumen, maintain esophageal patency, and alleviate patient symptoms. Currently, self-expandable metallic stents (SEMS) with polymer-coated membranes that provide therapeutic benefits are the most commonly used stents in clinical practice, but their effectiveness is not ideal. The reasons are as follows: Stents lack the function of actively inhibiting tumor growth or their long-term inhibitory effect is unstable. Existing photodynamic therapy (PDT) stents loaded with photosensitizers (PSs) provide esophageal support and therapeutic functions; however, PSs are easily released or leaked in the tumor environment, and simply doping with PSs can easily lead to excessive spontaneous release, making it difficult to guarantee long-term efficacy. PS doping also limits the transmission time and distance of generated reactive oxygen species (ROS), typically with a transmission time of 14 μs and a transmission distance of less than 150 nm. Simultaneously, continuous tumor progression increases the risk of endothelial rupture, leading to esophageal restenosis. Furthermore, existing stents lack responsive channels to the tumor microenvironment (TME), resulting in poor therapeutic effects for esophageal cancer. Therefore, improving existing esophageal stents to meet clinical needs and enhance the efficacy of anti-tumor therapy is of significant research importance. Summary of the Invention

[0004] The purpose of this invention is to solve the above-mentioned technical problems and provide a photosensitizer-immobilized esophageal stent coating, which can have higher stability and esophageal cancer tumor inhibition effect. Another purpose of this invention is to provide the preparation and application of the photosensitizer-immobilized esophageal stent coating.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: A photosensitizer-immobilized esophageal stent coating based on a zirconium-based metal-organic framework is disclosed. The photosensitizer-immobilized esophageal stent coating comprises a nitric acid / polyethyleneimine intermediate adhesive layer, a PCN-224 NPs photodynamic layer disposed on the intermediate adhesive layer, and a MnO2 smart response channel layer disposed on the photodynamic layer for in-situ reaction to alleviate hypoxia. In the PCN-224 NPs photodynamic layer, Zr ions bind to the phenolic hydroxyl groups of the nitric acid / polyethyleneimine intermediate adhesive layer and are fixed on the surface of the TA / PEI adhesive layer. The PCN-224 NPs photodynamic layer is loaded with a photosensitizer.

[0006] Furthermore, the photosensitizer is a porphyrin photosensitizer, AlPcS4, Fe-TCPP nMOFs, UCNPs@PorphyrinMOFs, or Cu-MOFs.

[0007] Furthermore, the photosensitizer-immobilized esophageal stent coating is excited by a laser, and the laser conditions are: wavelength 600~1000 nm, irradiation intensity 30~60 mW / cm², and action time 5~20 min; preferably, the laser conditions are: wavelength 630 nm, irradiation intensity 50 mW / cm², and action time 10 min.

[0008] Furthermore, the photosensitizer-immobilized esophageal stent coating is a stent morphology placed at the site of the patient's esophageal tumor.

[0009] This invention provides a method for preparing the above-mentioned photosensitizer-immobilized esophageal stent coating, comprising the following steps: S1. Preparation of zirconium-based metal-organic framework PCN-224 NPs ZrOCl2·8H2O, benzoic acid solution and TCPP were mixed in a weight ratio of (10~30):(1000~2000):(100~200) and stirred at 80~100℃ for 5~6 h to obtain PCN-224 NPs; S2. Preparation of polyphenol-assisted adhesive layer TA / PEI@PET The PET film of the integrated braided scaffold was immersed in a buffer solution with a concentration of 0.4~0.8 mg / mL TA. After mixing and reacting for 1~4 h, PEI was added to make its concentration 5~20 mg / mL. The pH was adjusted to 7.0~9.0. After mixing and reacting for 1~4 h, the TA / PEI@PET film was obtained. S3. Fabrication of the scaffold photodynamic layer PCN-224 NPs@TP The TA / PEI@PET film was immersed in a PCN-224 NPs HEPES solution with a concentration of 0.5~2.0 mg / mL to co-deposit the scaffold photodynamic layer PCN-224 NPs@TP; S4. Preparation of the hypoxia relief layer PCN-224 NPs@TP was immersed in a MnCl2 solution with a concentration of 2.5~10.0 mg / mL and reacted at pH 9~10 for 0.1~1 h to obtain a photosensitizer-immobilized esophageal stent coating.

[0010] Furthermore, the PET coating of the integrated braided bracket is prepared by the following method: NiTi spring yarn and PET yarn are regularly braided, with a braiding angle of 55~58°, a braiding pitch of 3.9~4.7 inches, and an inner diameter of 8~10 mm; the PET coating thickness is 0.46~0.50 mm; the NiTi spring yarn is a spring structure composed of NiTi alloy yarn heated and shaped, with a diameter of 0.1~0.3 mm; the number of NiTi spring yarns is 8~12, and the pitch of the NiTi spring yarn is 1.0~3.0 mm; the PET yarn is a PET multifilament composed of monofilaments with a linear density of 500~1500 D and 144~288 f.

[0011] Preferably, the PET coating of the integrated braided bracket is prepared by the following method: NiTi spring yarn and PET yarn are regularly braided together at a braiding angle of 58°, a braiding pitch of 4.6 inches, and an inner diameter of 9 mm; the PET coating thickness is 0.48 mm; the NiTi spring yarn is a spring structure composed of NiTi alloy yarn heated and shaped, with a diameter of 0.2 mm; the number of NiTi spring yarns is 12, and the pitch of the NiTi spring yarn is 2.0 mm; the PET yarn is a PET multifilament composed of 192 f monofilaments with a linear density of 1000 D.

[0012] This invention seeks protection for the use of the above-described photosensitizer-immobilized esophageal stent coating in the preparation of medical devices for tumor treatment.

[0013] Furthermore, the tumor is esophageal cancer or other stricture tumor lesions.

[0014] Furthermore, the tumor microenvironment exhibits the following changes: hypoxia, acidic pH changes, and endogenous H2O2 production.

[0015] The present invention provides a photosensitizer-immobilized esophageal stent, the stent comprising the above-described photosensitizer-immobilized esophageal stent coating.

[0016] The beneficial effects of this invention are as follows: (1) The photosensitizer-immobilized esophageal stent coating of this invention functionalizes the PET film surface of the stent through a tannic acid / polyethyleneimine (TA / PEI) intermediate adhesion layer, PCN-224 NPs as a photodynamic layer, and MnO2 as a hypoxia relief layer. This photosensitizer-immobilized esophageal stent coating can stably exist in tumor tissue, with a retention time of up to 4 weeks (retention rate of 90.63%), effectively overcoming the challenge of large-scale release during intraluminal PDT. After immersion in a simulated tumor acidic environment for 28 days, it still generates sufficient reactive oxygen species after irradiation to kill 89.50% of tumor cells, providing good therapeutic effects; and significantly improves the tumor hypoxic environment, thereby enhancing the efficacy of PDT.

[0017] (2) The photosensitizer-immobilized esophageal stent coating of the present invention can trigger a photochemical reaction under light conditions, effectively kill tumor cells, and has safety and biocompatibility; and can take effect according to the tumor microenvironment, such as hypoxia, acidic pH and endogenous H2O2, with more precise targeting effect, and has great application potential in the local treatment of malignant esophageal tumors, providing more effective and personalized treatment options for esophageal tumor patients. Attached Figure Description

[0018] Figure 1 This diagram illustrates the preparation and application principle of PTPM.

[0019] Figure 2 SEM image of PCN-224 NPs (a); histogram of particle size distribution (b); TEM image (c); STEM-EDS elemental mapping of C, N, O and Zr (d).

[0020] Figure 3 XRD pattern of PCN-224 NPs (a); ATR-FTIR spectrum of PCN-224 NPs (b); UV-Vis pattern of PCN-224 NPs and TCPP powder (c).

[0021] Figure 4 N2 adsorption-desorption isotherms of PCN-224 NPs (a); pore size distribution curve of PCN-224 NPs (b); ROS generated by PCN-224 NPs under 630 nm laser irradiation (50 mW / cm², 10 min) (c).

[0022] Figure 5SEM images and corresponding magnified images of TA-PEI membrane (a); SEM images and corresponding magnified images of TA / PEI membrane (b); XPS analysis of TA-PEI membrane (c); XPS analysis of TA / PEI membrane (d); Schematic diagram of the synthesis process of TA-PEI and TA / PEI membrane samples (e); SEM images of PCN-224 NPs@TA-PEI (f)-(g).

[0023] Figure 6 Schematic diagram of PT and PTP preparation (a); SEM images of PTP prepared with different concentrations of PCN-224 NPs (bd).

[0024] Figure 7 ATR-FTIR spectra of PET, PT, and PTP samples; amplified ATR-FTIR spectra of PET, PT, and PTP (a); elemental analysis of PET, PT, and PTP samples by XPS (b).

[0025] Figure 8 The curves show the relative absorbance of DPBF solutions of different samples at 410 nm as a function of irradiation time.

[0026] Figure 9 The results show the viability of TE-1 cells after irradiating PTP with 630 nm lasers of different power densities for 10 min.

[0027] Figure 10 SEM images of PTP after incubation in PBS at different pH values ​​for several days (a); digital images of PTP after incubation in PBS at different pH values ​​for 1, 4, 7, 14 and 28 days (b).

[0028] Figure 11 Oxidation spectra of DPBF solutions treated with PTP under light irradiation, with PTP incubated with PBS (pH=7.4) for 28 days (a); Oxidation spectra of DPBF solutions treated with PTP under light irradiation, with PTP incubated with PBS (pH=6.5) for 28 days (b); Oxidation spectra of DPBF solutions treated with PTP under light irradiation, with untreated PTP (c); Oxidation spectra of DPBF solutions (10 μg / mL) under light irradiation (d).

[0029] Figure 12To compare the absorbance with that of unsoaked PTP, the relative absorbance at 410 nm of different PTP samples soaked in DPBF solution in PBS buffer (pH=6.5, 7.4) for different time periods under laser irradiation (630 nm, 50 mW / cm², 10 min) is shown in (a); the Zr content on the surface of different samples is shown in (b); and a schematic diagram of the TA / PEI adhesion layer stabilization mechanism and the PCN-224 NPs coating stabilization effect in PTP coating in PBS buffer at different pH values ​​is shown in (c).

[0030] Figure 13 SEM images (a) of PTPM prepared after mineralization at different MnCl2 concentrations (0, 2.5, 5.0 and 10.0 mg / mL); SEM-EDS mapping of PTPM (prepared at 5 mg / mL concentration) (b).

[0031] Figure 14 Images of actual PET, PTP, and PTPM samples.

[0032] Figure 15 The variation in O2 generated when PTPM is prepared in H2O2 (100 μM) solution with different concentrations of MnCl2 (a); O2 generation curves of PTPM reaction with different concentrations of H2O2 under acidic conditions (b); O2 generation after PTPM is treated in deoxygenated aqueous solution with different solutions of PBS at pH 7.4, PBS + H2O2 at pH 7.4, PBS at pH 6.5, and PBS + H2O2 at pH 6.5 (c).

[0033] Figure 16 A schematic diagram of the process of PTPM generating O2 to alleviate hypoxia in TE-1 cells (a); the generated O2 can alleviate the hypoxia in TE-1 cells (b); the O2 production in TE-1 cells treated with PTP plus 50 μM H2O2 and PTPM plus 50 μM H2O2 (c).

[0034] Figure 17 The relative absorption and changes at 410 nm of DPBF (dissolved in HAc-NaAc buffer) treated with PTP+laser, PTPM+laser, PTPM+H2O2 (100 μM)+laser (630 nm, 50 mW / cm²) and laser only are shown.

[0035] Figure 18 For biocompatibility. HFF activity after 1 day (a) and 3 days (b) of treatment with PET, PTP and PTPM; Calcein-AM / PI images of different samples after 1 day and 3 days (c).

[0036] Figure 19Results of viability assays for TE-1 cells cultured with different concentrations of H2O2.

[0037] Figure 20 The in vitro PDT effect. TE-1 cell viability under normoxic and hypoxic environments with or without laser irradiation (630 nm, 50 mW / cm², 10 min), treated with (I) 50 μM H₂O₂, (II) PTP plus 50 μM H₂O₂, and (III) PTPM plus 50 μM H₂O₂; conditions are expressed as D (dark), L (bright), N (normooxic), and H (hypoxic).

[0038] Figure 21 Schematic diagram of in vitro PDT treatment experiment (a); TE-1 cells were treated with PTP plus 50 μM H2O2 and PTPM plus 50 μM H2O2 in the absence of light and O2, and then irradiated (630 nm, 50 mW / cm², 10 min), and ROS generation diagram (b); TE-1 cells stained with Calcein-AM / PI were treated with 50 μM H2O2, PTP plus 50 μM H2O2 and PTPM plus 50 μM H2O2 under normoxic and hypoxic conditions, respectively, and then irradiated with laser (630 nm, 50 mW / cm², 10 min), and cell viability after treatment (c).

[0039] Figure 22 To validate the long-acting PDT capability in vitro. Survival rate of TE-1 cells co-cultured with PTP (immersed in PBS solution simulating TME for 28 days) and after laser irradiation (630 nm, 50 mW / cm², 10 min) (a); corresponding fluorescence images of Calcein-AM / PI staining (b).

[0040] Figure 23 This is a diagram illustrating the entire process of sample implantation and treatment.

[0041] Figure 24 Images of HIF-1α stained tumors in nude mice from different treatment groups, scale bar = 200 μm; the symbol "+" represents laser irradiation.

[0042] Figure 25 This is a schematic diagram of the treatment plan for KYSE xenograft tumor model mice.

[0043] Figure 26 Tumor growth curves of KYSE tumor-bearing nude mice after treatment with PET, PTP, and PTPM (with or without laser irradiation) (left panel); tumor weight of mice in each group after treatment (right panel).

[0044] Figure 27Photos of different groups of nude mice before and 12 days after treatment.

[0045] Figure 28 H&E, TUNEL, and Ki67 stained images of tumors removed in nude mice from different treatment groups. "+" indicates laser irradiation.

[0046] Figure 29 The curves showing the changes in body weight of KYSE tumor-bearing mice in different groups.

[0047] Figure 30 Histological analysis of major organs in nude mice after different treatment groups (PET, PTP+laser, PTPM, PTPM+laser).

[0048] Figure 31 Biochemical analysis of serum ALT (a), AST (b), BUN (c), and CREA (d) in mice under different treatment regimens. Detailed Implementation

[0049] To enable those skilled in the art to better understand the present invention, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.

[0050] The reagents, instruments, and specifications used in the following examples are shown in Tables 1 and 2.

[0051] Table 1. Detailed information on experimental materials and reagents

[0052] Table 2 Detailed information on instruments and equipment used in the experiment

[0053] Unless otherwise specified, all experiments in the examples were performed in at least three replicates. Quantitative results are expressed as mean ± standard deviation. Statistical analysis between groups was performed using one-way ANOVA and Student's t-test. p A value <0.05 indicates a statistically significant difference. p <0.05 (*) p <0.01 (**), p <0.001 (***).

[0054] Example 1: A photosensitizer-immobilized esophageal stent coating based on a zirconium-based metal-organic framework and its preparation. This embodiment provides a functional composite coating PTPM for esophageal tumor stents. The composite coating includes a tannic acid / polyethyleneimine (TA / PEI) intermediate adhesive layer, a PCN-224 NPs photodynamic layer disposed on the intermediate adhesive layer, and a MnO2 smart response channel layer disposed on the photodynamic layer for in-situ response to relieve hypoxia. The intermediate adhesive layer is configured as a stent and is disposed at the esophageal tumor site of the patient.

[0055] like Figure 1 As shown, the preparation method of the functional composite coating PTPM is as follows: First, a uniform TA / PEI intermediate adhesive layer is prepared, wherein TA and PEI form strong adhesion sites through Schiff base reaction and electrostatic interaction; a photosensitizer is loaded using PCN-224 NPs, and the self-quenching of the porphyrin photosensitizer is prevented and enhanced. 1 The diffusion of O2 effectively generates [something] under laser irradiation. 1 O2; furthermore, Zr ions in PCN-224 NPs coordinate with the phenolic hydroxyl groups on the surface of the TA / PEI intermediate adhesive layer, thereby fixing them to the TA / PEI adhesive layer surface. Based on the Schiff base (C=N) bond in TA / PEI and the coordination bond between TA and MOF, stability is maintained under different pH conditions. A MnO2 coating is introduced as a smart responsive channel layer. In acidic, H2O2-rich TME, the in-situ reaction of the MnO2 coating triggers the opening of inorganic channels, alleviating hypoxia and enhancing ROS generation. Simultaneously, it acts as a protective barrier in non-tumor esophageal tissue.

[0056] The specific preparation method is as follows: (1) Preparation of zirconium-based metal-organic frameworks (PCN-224 NPs) ZrOCl2·8H2O solution (20 mg, dissolved in 10 mL DMF), benzoic acid solution (1400 mg, benzoic acid powder dissolved in 20 mL DMF), and TCPP solution (150 mg, dissolved in 20 mL DMF) were mixed and stirred at 90 °C for 5.5 h. After cooling to room temperature, the mixture was centrifuged at 12,000 rpm for 30 min, and the resulting particles were collected and washed three times with acetone to obtain PCN-224NPs. The synthesized PCN-224 NPs were redispersed in DMF for further use.

[0057] (2) Preparation of polyphenol-assisted adhesive layer Preparation of TA / PEI@PET (TP) membrane: The PET film of the integrated braided scaffold was coated (cut into circular pieces with a diameter of 1.25 cm). It was immersed in 16 mL of Tris buffer (5 mM, pH 6.0) containing 0.625 mg / mL TA and stirred for 2 h. Then, 4 mL of PEI aqueous solution (10 mg / mL) was quickly added, and the pH was adjusted to 8.0 with NaOH. The mixture was stirred for another 2 h at room temperature. The resulting TA / PEI@PET (TP) membrane was then removed, washed three times with deionized water, and vacuum dried for later use.

[0058] The PET coating of the integrated braided scaffold is prepared by the following method: NiTi spring yarn and PET yarn are regularly braided with a braiding angle of 58°, a braiding pitch of 4.6 inches, and an inner diameter of 9 mm; the PET coating thickness is 0.48 mm; the NiTi spring yarn is a spring structure composed of NiTi alloy yarn heated and shaped, with a diameter of 0.2 mm; the number of NiTi spring yarns is 12, and the pitch of the NiTi spring yarn is 2.0 mm; the PET yarn is a PET multifilament composed of 192 f monofilaments with a linear density of 1000 D.

[0059] TA-PEI membrane preparation: A PET-coated integrated braided scaffold (cut into 1.25 cm diameter discs) was immersed in 16 mL of Tris buffer (5 mM, pH 6.0) containing 0.625 mg / mL TA. After stirring for 2 h, 4 mL of PEI aqueous solution (10 mg / mL) was rapidly added, and the pH was adjusted to 6.0 with NaOH. Stirring continued for 2 h at room temperature. The resulting TA-PEI membrane was then removed, washed with deionized water, and vacuum dried for later use.

[0060] (3) Fabrication of the photodynamic layer of the scaffold PCN-224 NPs were dispersed in HEPES solution and sonicated for 1 h to prepare a homogeneous mixture. The TP membrane was then immersed in PCN-224 NPs solutions of different concentrations (0.5, 1.0, and 2.0 mg / mL) for 0.5 h to complete the co-deposition process. The resulting sample was designated PTP (PCN-224 NPs@TP). The PTP membrane was then dried in a vacuum oven at 30 °C for 24 h and stored in the dark.

[0061] (4) Preparation of hypoxia relief layer PTPM (MnO2@PTP) was obtained through in-situ mineralization of MnO2 based on PTP (1.25 cm diameter discs). Specifically, the PTP membrane was immersed in 2.5, 5.0, and 10.0 mg / mL MnCl2 solutions and gently stirred for 1 h. The pH of the solution was then adjusted to 10.0 using NaOH (5.0 M), and the mixture was stirred for another 20 min. The prepared PTPM samples were thoroughly washed with water and vacuum dried at 37 °C to obtain a functional composite coating for esophageal tumor stents, namely, a photosensitizer-immobilized esophageal stent coating based on a zirconium-based metal-organic framework.

[0062] Example 2: Physicochemical property characterization and stability testing of the stent 1. Testing Method (1) Physicochemical properties characterization of photosensitizer-immobilized esophageal stent coating SEM images were obtained using a Hitachi SU8010 scanning electron microscope at an accelerating voltage of 5 kV. TEM was obtained using a Talos F200S transmission electron microscope. XRD data were recorded on a Bruker X-ray diffractometer, with a 2θ range of 0–30°. ATR-FTIR spectra were acquired using a Nicolet 6700. UV-Vis spectra were measured using a TV-1901 UV-Vis spectrometer. BET and pore size distributions were recorded using a fully automated rapid surface area and porosity analyzer. XPS spectra of the samples were analyzed using an Escalab 250Xi. O2 generation was detected and performed on a JPB-607A. PDT photoexcitation was performed using a 630 nm laser. Specifically, DPBF was used as a probe for measurement. 1 O2 generation. Observe the fluorescence microscope image on a fluorescence microscope.

[0063] (2) Stability test of photodynamic coating PTP samples (cut into 1.25 cm diameter discs) were evenly divided into four parts and immersed in PBS buffer (pH 6.5 or 7.4). The surface morphology of the samples after immersion for different times was characterized by SEM. The PTP coating was monitored at different time intervals using UV-Vis. 1 O2 generation. In addition, the Zr content of different PTP films after different immersion times was measured by ICP to quantitatively evaluate whether PCN-224 NPs can be stably bonded to the PET fiber surface.

[0064] (3) Reactive oxygen species generation test In the experiment measuring ROS generation, DPBF was used to detect ¹O₂ generated on PTP. A nitrogen-air-purified DPBF solution (0.01 M HAc-NaAc buffer) was purged for 30 min to create an anaerobic environment. The specific procedure was as follows: PTP, PTPM (a 1.25 cm diameter disc), and 100 μM H₂O₂ were immersed in the DPBF solution and irradiated with a 630 nm laser (50 mW / cm²). The absorbance of the DPBF at 410 nm was measured at different time intervals.

[0065] (4) Oxygen production test O2 generation was measured using a dissolved oxygen meter. In short, PTPM samples were added to 15 mL of 100 μM H2O2 solution at different pH values ​​(pH=6.5, 7.4). The solution was gently stirred to remove pre-existing dissolved O2. Nitrogen gas was bubbled through the H2O2 solution for 30 min before adding the PTPM samples. The dissolved O2 concentration in the centrifuge tubes was measured every 2 min. Dissolved O2 in PBS was used as a control.

[0066] HFF cells and esophageal squamous cell carcinoma cells (TE-1 cells) were purchased from the Cell Bank of the Chinese Academy of Sciences (Shanghai). HFF cells were used to evaluate cell compatibility; their culture medium consisted of 90% DMEM, 10% FBS, and 1% penicillin / streptomycin. HFF cells were then cultured in a cell culture incubator. The culture medium was changed every two days. When cell confluence reached 80%–90%, cells were digested with EDTA and passaged or seeded at a 1:2 dilution. TE-1 cells were used to evaluate tumor suppressor activity; their culture medium consisted of 90% RPMI 1640, 10% FBS, and 1% penicillin / streptomycin. TE-1 cells were then cultured in a cell culture incubator. The culture medium was changed every two days. When cell confluence reached 80%–90%, cells were digested with EDTA and passaged or seeded at a 1:2 dilution. The cell culture incubator conditions were set at 37 °C and 5% CO2. All experimental samples were sterilized by irradiation under ultraviolet light for 2 hours and then placed in 24-well plates in a laminar flow hood for later use.

[0067] (5) Cell compatibility The CCK-8 assay was used to evaluate the biocompatibility of different samples (PET, PTP, PTPM coated discs, 1.25 cm in diameter). HFF cells were loaded at 2 × 10⁻⁶ cells / cm². 4Cells were seeded at a density of 1:1 in 24-well plates and incubated for 24 h. Subsequently, sterilized samples were placed into the plates. After incubation for 24 or 72 h, the medium was replaced with 100 μL of fresh medium containing 10% CCK-8, and the cells were incubated for another 2 h. Cells cultured in medium only were used as a control. The absorbance of the relevant cells was measured at 450 nm using a microplate spectrophotometer to calculate relative cell viability.

[0068] (6) Intracellular oxygen measurement Esophageal squamous cell carcinoma TE-1 cells (2×10) 4 Cells (cells / well) were seeded in confocal culture dishes and incubated in a hypoxic bag (1% O2, 5% CO2 and 94% nitrogen) for 12 h. Samples (PET, PTP and PTPM coated discs, 1.25 cm in diameter) were then added and incubated for 8 h. Cells were washed with PBS and then incubated with Ru(dpp)3]Cl2 for 4 h. Cells were then exposed to light (630 nm, 50 mW / cm²) for 10 min or kept in the dark for 10 min. After washing three times with PBS, the cells were observed using CLSM. (DAPI, Ex: 405 nm, Em: 488 nm; [Ru(dpp)3]Cl2, Ex: 488 nm, Em: 620 nm).

[0069] (7) Measurement of intracellular reactive oxygen species levels TE-1 cells were loaded at 2×10 4 Cells were seeded at a density per well in 24-well plates and cultured overnight under hypoxic conditions. Cells were co-cultured with different samples (PET, PTP, and PTPM coated discs, 1.25 cm in diameter) for 4 h, after which the samples were removed. Cells were then washed three times with PBS, stained with DCFH-DA dye, and incubated at 37 °C for 30 min. The cells were then irradiated with a 630 nm laser (50 mW / cm²) for 10 min. Cells were subsequently observed using fluorescence microscopy to assess intracellular ROS levels. The excitation wavelength and emission filter for DCFH-DA were 488 nm and 500-550 nm, respectively. For comparison, cells treated with PET coating were also stained with DCFH-DA.

[0070] (8) In vitro phototoxicity test Evaluation of PDT effect of PTP samples under different light power densities: TE-1 cells were used at 5 × 10⁻⁶ cells per well. 4Cells were seeded at high density and cultured for 24 h, then co-cultured with sterilized PTP samples. Irradiation was performed for 10 min at different light power densities (20, 35, and 50 mW / cm²). After 24 h of incubation, cells were washed three times with PBS, and cell viability was measured using the CCK-8 assay to assess the phototoxicity of PTP samples to TE-1 cells.

[0071] Evaluation of PDT effect on PET, PTP and PTPM samples: To verify the phototoxicity of the coating, TE-1 cells were injected at a density of 5 × 10⁻⁶ cells per well. 4 Cells were seeded at a density in 24-well plates and cultured overnight. The cells were then co-cultured with different samples (PET, PTP, and PTPM) in the dark for 12 h. Afterward, all cells were irradiated with a 630 nm laser (50 mW / cm²) for 10 min and kept in the dark. For hypoxia assays, TE-1 cells were seeded in 24-well plates and cultured overnight. After adding the sample, a hypoxia bag was added to the culture chamber to create a hypoxic environment (1% O2), and the cells were cultured for 12 h. The cells were then irradiated with a 630 nm laser (50 mW / cm²) for 10 min and kept in the dark.

[0072] In vitro phototoxicity was quantitatively and qualitatively assessed using the CCK-8 assay kit and Calcein-AM / PI staining. Cell viability was determined and calculated for various samples using the CCK-8 kit. Cell killing ability was assessed by direct observation under a fluorescence microscope after staining with the Calcein / PI kit.

[0073] 2. Experimental Results (1) Surface morphology and composition characterization of PCN-224 NPs like Figure 2 As shown in (a) and (b), PCN-224 NPs exhibit a uniform spherical morphology with an average diameter of 82.87 ± 13.17 nm. Furthermore, elemental mapping images ( Figure 2 (c) and (d) show that C, N, O and Zr elements are evenly distributed.

[0074] To further investigate the synthesis of PCN-224 NPs, they were characterized using XRD, ATR-FTIR, and UV-vis spectroscopy. XRD showed ( Figure 3(a) The peaks at 4.60°, 6.39°, 7.87°, 9.06°, and 11.16° correspond to the (0 0 2), (0 2 2), (2 2 2), (0 0 4), and (2 2 4) crystal planes, respectively, confirming the formation of PCN-224 NPs. In the ATR-FTIR spectrum of PCN-224 NPs, at 3437 cm⁻¹... -1 and 3325 cm -1 The peaks at 1544-1605 cm⁻¹ are attributed to the stretching vibrations of the –OH and N-H groups in TCPP. -1 Stretching vibrations corresponding to the C=C bonds in benzene rings and pyrroles were also observed nearby. At 1653 cm⁻¹ - The strong vibrational peak at position ¹ indicates coordination with metal ions ( Figure 3 (b)). Furthermore, at 655 cm... - A peak corresponding to the Zr–OH bond vibration was observed at position ¹. ATR-FTIR results also confirmed the chemical structure of PCN-224 NPs. Subsequently, UV-vis spectral analysis of TCPP and PCN-224 NPs was performed. Figure 3 (c) The results show that the TCPP spectrum exhibits a main Soret peak at 419 nm and four Q bands at 515, 552, 590, and 645 nm. For PCN-224 NPs, the main Soret peak appears at 421 nm, and the four Q bands are located at 518, 552, 592, and 650 nm. Compared with TCPP, the four Q bands of PCN-224 NPs show a slight redshift, which may be due to the coordination between TCPP and the Zr6 cluster. All these results confirm the successful synthesis of PCN-224 NPs.

[0075] Furthermore, the porous structure of PCN-224 NPs was analyzed using N2 adsorption-desorption isotherms. The surface area, measured by BET, was 382.16 m² / g. Figure 4 (a)). The average pore size determined by BJH analysis was 1.96 nm. Figure 4 (b)). These findings indicate that PCN-224 NPs possess an excellent porous structure, which facilitates the efficient diffusion of ¹O₂. To assess ¹O₂ generation under laser irradiation, DPBF was used as a ROS detection probe. When the DPBF solution incubated with PCN-224 NPs was irradiated with a laser (630 nm; 50 mW / cm²), the absorbance at 410 nm decreased by 47.50% after 10 min. Figure 4 (c)). This result demonstrates that PCN-224 NPs have the ability to generate ¹O2 and exhibit photoinduced PDT effect as PSs.

[0076] (2) Preparation of polyphenol adhesive layer TA and PEI adhesive layers were synthesized under two different pH conditions: pH 6.0 / 6.0 (denoted as TA-PEI) and pH 6.0 / 8.0 (denoted as TA / PEI). The morphology of the coatings formed under different pH conditions was observed using SEM, and the assembly process and molecular interactions between polyphenols and polyamines were investigated using XPS. Figure 5 As shown in (a), TAPEEI forms discrete small aggregates and deposits on the PET fiber surface, resulting in an uneven coating morphology. In contrast, TA / PEI produces a continuous and uniform film on the substrate, indicating improved coating uniformity and adhesion. Figure 5 (b) Surface chemical elements and valence states of TA-PEI and TA / PEI coatings were characterized using XPS. Figure 5 (c) and (d)). High-resolution N 1s spectra of the TA-PEI coating indicate that, under pH 6.0 / 6.0 conditions, TA and PEI primarily interact through electrostatic forces. Conversely, the N 1s spectra of the TA / PEI coating show that, at pH 6.0 / 8.0, TA and PEI simultaneously participate in electrostatic interactions and covalent C=N bonding (399.8 eV), thereby enhancing the coating's stability and adhesion. Potential molecular structures under different conditions are shown below. Figure 5 As shown in (e).

[0077] SEM imaging was used to characterize the morphology of the PCN-224 NPs@TA-PEI and PCN-224 NPs@TA / PEI coatings. For example... Figure 5 As shown in (f) and (g), PCN-224 NPs can be assembled on both TA-PEI and TA / PEI layers. However, in the TA-PEI coating, PCN-224 NPs aggregate into large and unevenly distributed clusters on the intermediate adhesive layer. Conversely, due to the uniform distribution in the TA / PEI intermediate adhesive layer, the PCN-224 NPs@TA / PEI coating exhibits uniform deposition on the substrate.

[0078] The PCN-224 NPs coating was prepared using a simple and effective self-assembly method. Figure 6 (a) Specifically, TA / PEI was first bonded to the surface of PET fibers as an intermediate adhesive layer to obtain PT samples. PT was then immersed in a PCN-224 NPs solution, and highly dispersed nanoparticles were deposited on the TA / PEI intermediate adhesive layer to form a PCN-224 NPs coating. The surface morphology of the PT samples assembled with three different concentrations of PCN-224 NPs was observed by SEM. Figure 6(b), (c), and (d)). When the concentration of PCN-224NPs was 0.5 mg / mL, the loading decreased accordingly. When the assembly concentration increased to 1.0 mg / mL, the spherical nanoparticles uniformly covered the fibers. Figure 6 (c) After assembling 2.0 mg / mL PCN-224 NPs, aggregates formed at the fiber junctions, resulting in uneven distribution. This was mainly due to the excessively high concentration of PCN-224 NPs in the dispersion, leading to agglomeration. Figure 6 (d)). These findings suggest that the TA / PEI intermediate adhesive layer facilitates an efficient assembly process, thereby securing PCN-224 NPs to the support coating surface.

[0079] In addition, the surface chemical structures of three different films were analyzed by ATR-FTIR. Figure 7 (a) The ATR-FTIR spectrum of PT film did not change significantly compared to that of PET, which may be due to the low TA / PEI coating content on the fiber surface. In the ATR-FTIR spectrum of PTP, at a wavenumber of 1605 cm⁻¹... - ¹ A tensile vibration peak of the C=C bond in the pyrrole ring was observed nearby, confirming the successful loading of PCN-224 NPs. Furthermore, the elemental composition of different sample surfaces was confirmed by XPS. Figure 7 As shown in (b), all samples exhibited similar characteristic peaks of O 1s (532.1 eV) and C 1s (285.0 eV) in the broad scan spectrum. Compared with the original PET, the PT sample showed a novel N 1s (400.3 eV) peak, which can be attributed to the assembled TA / PEI. Meanwhile, for PTP, Zr peaks appeared at 185.2 eV and 333.4 eV. These results confirm the successful construction of PCN-224 NPs on the PET surface.

[0080] exist 1 DPBF oxidizes in the presence of O2. DPBF was used as a probe to evaluate the formation of PTP coatings under laser irradiation (630 nm; 50 mW / cm²). 1 The case of O2. For example... Figure 8As shown, when DPBF is used alone, its absorbance decreases slightly by 2.70% after irradiation with a 630 nm laser (50 mW / cm²), due to self-degradation. When DPBF reacts with PET and PT, the absorbance decreases by 2.22% and 3.15% respectively after irradiation with a 630 nm laser, indicating that PET and PT have no significant effect on DPBF. Conversely, when irradiating PTP0.5, PTP1.0, and PTP2.0 samples, the absorbance of DPBF decreases by 16.38%, 24.30%, and 42.88% respectively, with PTP1.0 exhibiting excellent 1O2 generation performance. ICP-MS analysis shows that the Zr content of PTP2.0 (5.02 mg / g) is significantly higher than that of PTP1.0 (2.72 mg / g), which is attributed to the aggregation behavior of PCN-224 NPs affecting the quantum yield. PTP1.0 was selected as the representative sample for subsequent experiments, and is referred to as PTP for short.

[0081] The in vitro PDT efficiency of PTP under different optical power density irradiation was evaluated using CCK-8 experiments. Figure 9 When treated with PTP alone, 96.76 ± 6.90% of TE-1 cells survived without light, while 59.40 ± 6.5% survived under laser irradiation at a power density of 20 mW / cm². At a power density of 35 mW / cm², the survival rate decreased to 29.40 ± 0.10%. Under irradiation with a 630 nm laser at 50 mW / cm², only 9.40 ± 0.20% of cells survived. These results indicate that under sufficient O2 conditions, cytotoxicity increases with increasing light power density, and the ROS generated under irradiation at 50 mW / cm² exhibits a strong anti-tumor effect.

[0082] (3) Stability study TME possesses unique structural and compositional characteristics, including hypoxic conditions, acidic pH (6.5–6.8), and excess endogenous H₂O₂ (0–100 μM). Therefore, in this study, PTP was immersed in PBS at different pH values ​​(7.4 and 6.5) to simulate the conditions of normal tissue environment and TME, and to assess the stability of PTP. To observe the retention of PCN-224 NPs on the PTP surface, SEM was used to characterize PTP samples after different immersion times.

[0083] like Figure 10 As shown in (a), even after soaking for 28 days, a large number of PCN-224 NPs were still present on the PTP surface, indicating that PTP remained stable under both normal and TME conditions. Figure 10(b) Digital images of PTP in PBS at different pH values ​​over 1, 4, 7, 14 and 28 days are shown. No color change was observed in the solution, indicating that only a small number of PCN-224 NPs detached after soaking.

[0084] To investigate the photodynamic effects of PTP after 28 days of immersion in simulated normal esophagus and tumor conditions in vitro, laser irradiation (630 nm, 50 mW / cm²) was performed. 2 The amount of ROS generated in DPBF solution under real-time conditions was determined. The results showed that with increasing illumination time (0-10 min), both the PTP group (immersed in PBS (pH=7.4) for 28 days, immersed in PBS (pH=6.5) for 28 days, and unimmersed) and the unimmersed PTP exhibited DPBF degradation, with a significant decrease in absorbance at 410 nm. Figure 11 (a), (b), and (c)). The DPBF solution, serving as a control group, showed virtually no change in absorbance after laser irradiation. Figure 11 (d) The above results show that PCN-224 NPs detached in small amounts, with most remaining on the PET fiber surface.

[0085] Figure 12 (a) The results showed that PTP maintained excellent ROS generation capacity and stability after 28 days. After laser irradiation for 10 min following PTP soaking in PBS solution for 28 days, the DPBF degradation rate reached 21.87±2.00% (pH=6.5) and 22.68±1.60% (pH=7.4). In contrast, the DPBF degradation rate after untreated PTP was 28.18±1.20%. Irradiation-induced DPBF degradation was 7.80±0.65%. Furthermore, ICP-MS results quantitatively verified the retention rate of PCN-224 NPs on the fiber surface (…). Figure 12 (c)). The results showed that the initial Zr content in PCN-224 NPs was 2.56 ± 0.20 mg / g. After soaking in liquid environments with different pH values ​​for 28 days, the Zr content was 2.36 ± 0.13 mg / g (pH=6.5) and 2.32 ± 0.27 mg / g (pH=7.4), with corresponding retention rates of 92.19% and 90.63%, respectively, which is 20.57% higher than the retention rate reported in the traditional PDT strategy. These results indicate that the TA and PEI adhesion layers remain stable at pH 6.5 and 7.4, which may be due to the low pH response of the C=N bond ( Figure 12 (c) Furthermore, in simulated tumor and normal tissue pH microenvironments, the coordination bonds between free phenols and metals in polyphenols remained relatively stable. These results indicate that PTP coatings exhibit excellent PSs retention.

[0086] (4) Evaluation of oxygen production capacity The MnO2 coating is the result of the mineralization reaction of MnCl2 on the PTP surface. First, the mineralization reaction results of different concentrations (0, 2.5, 5.0, and 10 mg / mL) of MnCl2 were observed under SEM. At a MnCl2 concentration of 5.0 mg / mL, the coating exhibited a uniform distribution (…). Figure 13 (a)), therefore this concentration was chosen as the concentration for subsequent experiments. EDS further confirmed the uniform distribution of O, Zr, and Mn on the PTPM coating. Figure 13 (b)). Furthermore, it was noted that the color of the prepared PTP surface changed from purple to brown. Figure 14 ).

[0087] Tumor-mediated transformation (TEM) is acidic (pH 6.5), with reactive oxygen species (ROS) concentrations within tumor cells approximately 100 times higher than in normal cells, while localized hypoxia is also observed in the tumor region. To more accurately investigate the oxygen production of materials in TEM and optimize PTPM coating parameters, single-factor experiments were conducted to explore the optimal MnCl2 and H2O2 concentrations, and to investigate the coating's effect in a pH 6.5 environment. First, the O2 generation capacity of PTPM prepared using different concentrations of MnCl2 (0, 2.5, 5.0, and 10.0 mg / mL) was investigated. It was observed that the amount of O2 generated increased over time, reaching a maximum of 2.5 ± 0.3 mg / mL when the MnCl2 concentration was 5.0 mg / mL. Figure 15 (a)). Subsequent experiments used PTPM membranes prepared at 5.0 mg / mL to simulate different concentrations of H2O2 (0, 50, 100 μM) in the TME, investigating the oxygen production from MnO2 degradation. Dissolved oxygen levels in the PTPM membranes were measured using a dissolved oxygen meter to be 0.9 ± 0.0, 2.5 ± 0.3, and 3.30 ± 0.1 mg / mL over 6 minutes. Figure 15 (b) To demonstrate the reactivity of the MnO2 coating within tumor tissue, the degradation of PTPM and O2 generation were studied in neutral and weakly acidic solutions under simulated physiological conditions of normal and tumor tissues. Figure 15 As shown in (c), the O2 concentration in the acidic solution containing both PTPM and H2O2 increased significantly from 0 mg / mL to 3.1 mg / mL within 10 min, while no significant O2 generation was observed in the acidic solution containing only PTPM, highlighting the importance of reactive oxygen species in the environment. Furthermore, no significant O2 generation was detected in the solution at pH 7.4, regardless of the presence of H2O2. The concentration of O2 generated in the presence of PTPM increased accordingly with increasing H2O2 concentration in the acidic solution. This O2 generation phenomenon can be explained by the following reaction: MnO₂ + H₂O₂ + 2H₂O + →Mn 2++2H₂O+O₂↑ The hypoxia probe [Ru(dpp)3]Cl2 emits red fluorescence under hypoxic conditions, used to assess O2 levels in TE-1 tumor cells after treatment with different sample groups. Fluorescence imaging ( Figure 16 (a) and (b) show that the red fluorescence of the PTPM group was significantly reduced compared with the control group and the PTP group, indicating that the MnO2 coating can alleviate hypoxia at the tumor site and help inhibit the tumor.

[0088] (5) Enhanced effect of reactive oxygen species Using DPBF as 1 O2 probe, measurement 1 The photodynamic effect was evaluated by assessing the amount of O2 generated. In an acidic environment containing H2O2, MnO2 decomposes to produce O2, which is enhanced under laser irradiation (630 nm; 50 mW / cm²). 1 O2 generation (38.89±1.46%) Figure 17 The above results indicate that PTPM enhances oxygen production capacity. 1 O2 generation improves PDT performance.

[0089] (6) Evaluation of in vitro tumor therapy The biocompatibility of PTPM coatings was assessed using HFF assays via CCK-8 kit and Calcein-AM / PI staining. Figure 18 The cell viability results shown in (a) and (b) indicate that HFF cells incubated with various samples for 24 and 72 h maintained a viability of over 90%, demonstrating that the PTPM samples exhibit excellent cell compatibility and have no adverse effect on normal cell proliferation. The results of the Calcein-AM / PI staining assay are consistent with those obtained using the CCK-8 kit. Figure 18 The surface shown exhibited a large amount of green fluorescence, and the staining experiment further provided a direct and visual verification of the significantly improved biocompatibility.

[0090] In addition, the effect of H2O2 concentration on cell viability was detected using a CCK-8 assay kit, and the results showed that relative viability exceeded 94% at a concentration of 50 μM. Figure 19 This indicates that the exogenous H2O2 concentration of 50 μM simulating TME in the phototoxicity experiment did not affect the viability of TE-1 cells.

[0091] The PDT-enhancing effect of PTPM was evaluated and verified under normoxic and hypoxic conditions. Figure 20Under normoxic conditions, both PTP and PTPM groups effectively killed cells via photodynamic therapy (PDT) after exposure to 630 nm laser irradiation, with cell viability rates of 8.65±0.99% and 9.18±1.04%, respectively. No cytotoxicity was observed in the absence of light irradiation, confirming the excellent PDT effect of PTP and PTPM coating. To further investigate the ability of MnO2 to enhance ROS production through O2 generation, TE-1 cells were treated with PTPM plus laser irradiation under both normoxic and hypoxic conditions. The results showed that PTPM plus laser irradiation effectively induced TE-1 cell death under both normoxic and hypoxic conditions. Compared with the PTP plus laser group under hypoxic conditions (38.02±7.20%), the cell viability rate of the PTPM group was significantly reduced to 11.67±2.99%. The enhanced photodynamic effect of PTPM under hypoxic conditions may be due to the O2 production from MnO2 decomposition.

[0092] Increased intracellular ROS can affect mitochondria, impacting cellular energy supply and leading to a decrease in adenosine triphosphate (ATP) levels, ultimately resulting in cell death. To further elucidate the mechanism of apoptosis, it was confirmed that ¹O2 was produced in TE-1 cells after PDT treatment. A schematic diagram of the effect of PTPM coating on cells is shown below. Figure 21 As shown in (a), the ROS probe DCFH-DA can be oxidized by ¹O2 to form DCF, emitting bright green fluorescence. Figure 21 (b) All experiments were conducted under hypoxic conditions and irradiated with a 630 nm laser. Cells treated with the laser alone showed no fluorescence, indicating minimal ROS generation. Furthermore, cells treated with PTPM showed significantly stronger green fluorescence compared to PTP. Since O2 is a key substrate for PDT, these results suggest that mineralized MnO2 plays a synergistic role in promoting O2 and ROS generation.

[0093] To observe cell viability, TE-1 cells were stained with Calcein-AM and PI to distinguish between live cells (green fluorescence) and dead cells (red fluorescence). Figure 21 As shown in (c), the control group fluorescence images showed only green fluorescence under both normoxic and hypoxic conditions. Under normoxic conditions, the fluorescence images of the PTP and PTPM groups mainly showed red fluorescence. However, under hypoxic conditions, cells treated with PTP showed more green fluorescence than cells treated with PTPM, consistent with the results detected by the CCK-8 kit. These results indicate that PTPM enhances oxygen supply due to its self-oxygenation function. 1 The amount of O2 produced is increased, thus making it more effective at killing tumor cells.

[0094] (7) Study on long-term in vitro tumor inhibition effect Furthermore, the photodynamic effect of PTP fibers after soaking was evaluated. TE-1 cells were co-cultured with PTP samples soaked in PBS solution simulating the pH of the tumor microenvironment for 28 days and then irradiated with a laser (630 nm, 50 mW / cm²). Notably, in the presence of H₂O₂, the cell viability of cells treated with PTP fibers was significantly reduced (10.50 ± 4.36%), confirming the sustained photodynamic effect of PTP. Figure 22 (a) Calcein-AM and PI staining further verified the cell state after PTP treatment. Extensive cell death showed red fluorescence, indicating that the PTP coating maintained its photodynamic efficiency even 28 days after in vitro release. Figure 22 (b) PTP fibers soaked for 28 days showed no significant difference in cell killing effect compared to the untreated PTP fibers (9.68±1.09%), and the cell killing rate was 20% higher than that of the previous study (30.50%), which highlights the stability and effectiveness of the long-acting PDT strategy.

[0095] Summary: The long-term effective inhibition of tumor cell proliferation by the stent is an important guarantee for reducing the incidence of restenosis. While existing PDT stents loaded with photosensitizers (PSs) provide esophageal support and therapeutic functions, PS leakage in the tumor environment makes it difficult to guarantee long-term efficacy. This embodiment proposes using a TA / PEI intermediate adhesion layer to assist in the stable loading of PCN-224 NPs, and further preparing a biocompatible MnO2 hypoxia relief layer to construct an esophageal stent coating for long-term PDT with PCN-224 NPs photosensitizer fixation. In vitro experiments were used to preliminarily explore the long-term effectiveness and enhanced PDT effect. The main conclusions are as follows: The sample in this embodiment can stably exist in tumor tissue, with PSs retention time up to 4 weeks and a retention rate as high as 90.63%, effectively overcoming the challenge of large-scale release during intraluminal PDT. A MnO2 coating was prepared by in-situ surface mineralization of the PTP coating using MnCl2, exhibiting cell compatibility. It can react with H2O2 in the acidic environment of the TME to generate O2, thereby alleviating cellular hypoxia and enhancing the oxygen-dependent photodynamic effect, thus increasing the cell-killing ability. Even under hypoxic conditions, cell viability decreased to 11.67±2.99%. In vitro results showed that it maintained its photodynamic efficiency even after 28 days of in vitro immersion. The immersion-treated coating still generated sufficient ROS to kill 10.50±4.36% of tumor cells, providing sustained therapeutic effects.

[0096] Example 3 Animal Verification Experiment 1. Experimental Methods (1) Animal grouping and ethical explanation Nude mice used in the experiments were purchased from Shanghai Bikaico Biotechnology Co., Ltd. Animal husbandry and experimental procedures were all conducted at the Laboratory Animal Center of Shanghai Pudong Hospital. All animal experiments underwent review by Shanghai Pudong Hospital regarding laboratory animal welfare and ethics, and the experimental procedures strictly adhered to animal experimental protocols. The 24 nude mice were randomly divided into the following four groups based on the type of sample placed on them: G1: Polyethylene terephthalate (PET) fiber model group (n=4); G2: PTP fiber group without laser irradiation (n=4); G3: PTPM fiber group without laser irradiation (n=4); G4: PTPM fiber group with laser irradiation (n=4).

[0097] (2) Construction of nude mouse tumor model The antitumor effect of photosensitizer-immobilized esophageal stent coatings on KYSE esophageal tumor cell xenograft nude mice was evaluated. Male BALB / c nude mice (4-5 weeks old, 18-20 g, Shanghai, China) were housed in a specific pathogen-free (SPF) laboratory at a temperature of 20-24 °C and a humidity of 44.5-51.8% with a 12-hour diurnal cycle. After one week of acclimatization, they were used for animal experiments. The KYSE esophageal tumor cell xenograft nude mice were constructed according to the following procedure: 1) When KYSE cells reach 80%–90% confluence in a culture dish, remove the culture medium, wash once with PBS, digest with 0.25% trypsin as usual, and repeatedly pipette to prepare a single-cell suspension. Then collect the suspension in a 10 mL centrifuge tube. Centrifuge at 1000 rpm for 3–5 min and discard the supernatant.

[0098] 2) Wash again with sterile PBS, centrifuge at 1000 rpm for 5 min, and discard the supernatant. Use trypan blue staining and cell counter to count cells. A viable cell count >95% indicates that the cell viability meets the experimental requirements.

[0099] 3) Cell seeding: Resuspend cells in PBS at a concentration of 1×10⁻⁶. 6 A density of 0.2 mL was injected subcutaneously into the right posterior buttock of nude mice, and mice with tumor volumes of approximately 150 mm³ were selected for inclusion in the study. Tumor volume was calculated using the following formula: V = (π / 6) × a 2 ×b Where a is the shortest diameter and b is the longest diameter.

[0100] 3) Evaluation method of photodynamic therapy in nude mouse ectopic esophageal tumor subcutaneous tumor model Implantation of coated samples: In this experiment, mice were divided into 4 groups (n=4): (1) PET-coated group; (2) PTP-coated group without laser irradiation; (3) PTPM-coated group without laser irradiation; (4) PTPM-coated group with laser irradiation. When the tumor volume reached approximately 150 mm... 3 At that time, PTP and PTPM membranes (0.4 × 0.4 cm) were surgically implanted into the tumor sites of nude mice. 2 ), and sutured.

[0101] PDT treatment: The laser group received a 660 nm laser (100 mW / cm²) 1-9 days after stent graft implantation. 2 The tumor site in mice was irradiated for 10 minutes every two days. Specifically, nude mice were first general anesthetized with pentobarbital solution, and the xenon lamp was positioned approximately 5 cm away from the tumor with a spot size of approximately 1.5 cm². 2 The output power of the optical fiber was measured using a power meter to ensure the accuracy of the light dose. The laser power density covering the tumor was 100 mW / cm². 2 The tumor volume was measured with calipers and the weight of the nude mice was weighed every two days.

[0102] In situ morphological changes in tumor tissue. Tumor tissue analysis after PDT. After treatment, all mice were sacrificed, tumor tissues were collected, fixed with paraformaldehyde, and embedded in paraffin. Histological analysis was performed after H&E staining. In tumor treatment, assessing tumor cell apoptosis through tissue biopsy combined with TUNEL assay, and analyzing proliferation activity using Ki67 immunohistochemistry, is a commonly used comprehensive assessment strategy in clinical and research settings. Immunohistochemical analysis was performed on paraffin-embedded sections, Ki67 antibody was used to detect proliferating cells, and TUNEL staining was used to assess cell apoptosis after PDT treatment. In addition, the collected tumor tissues were also stained with HIF-1α to assess tumor hypoxia after different treatments.

[0103] (4) Long-term in vivo toxicity testing In experimental animal studies, mouse blood samples were collected and biochemical indicators (such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), blood urea nitrogen (BUN), and creatinine (CREA)) were measured to assess liver and kidney function and metabolic status. Whole blood was collected from different groups of nude mice. After blood coagulation, serum was collected by centrifugation (4000 rpm, 30 min) for complete blood count and blood biochemical analysis. Liver function indicators in mice were defined as ALT values ​​ranging from 10.06 to 96.47 U / L and AST values ​​ranging from 36.31 to 235.48 U / L. Kidney function indicators were defined as UREA values ​​ranging from 3.9 to 12.4 mmol / L and CREA values ​​ranging from 10.91 to 85.09 µmol / L. Mice treated with physiological saline were used as controls. Major organs (heart, liver, spleen, lungs, and kidneys) were fixed with paraformaldehyde, and frozen sections were stained with H&E.

[0104] (5) Statistical analysis Statistical analysis: Quantitative data are presented as mean ± standard deviation and analyzed using one-way ANOVA. Two-tailed Student's t-tests were used for statistical analysis of the two groups. For all tests, p The value is considered statistically significant (*) p <0.05,** p <0.01, *** p <0.001).

[0105] 2. Experimental Results (1) Stent implantation and treatment To systematically evaluate the PTPM-coated samples in vivo and verify their PDT (prophylactic-to-transfer) efficacy, a KYSE xenograft tumor model was used. A sterile drape was laid on the operating table, and mice were first anesthetized. A 2cm incision was made at the tumor site on the back of the nude mouse, and three groups of coated samples (PET, PTP, and PTPM) were implanted into the tumor area through the incision. The incision was then sutured. The entire process of animal surgery, xenon lamp irradiation, and sample collection is as follows: Figure 23 As shown.

[0106] (2) Relief of hypoxia in the body HIF-1α is one of the most important transcription factors mediating cellular hypoxia responses. It regulates the expression of various target genes, producing a series of physiological effects to adapt to relatively hypoxic environments. It also participates in tumor growth, invasion, and metastasis, and can promote tumor cell survival by inhibiting tumor cell apoptosis under hypoxic conditions. The ability of PTPM to alleviate tumor hypoxia was assessed using a HIF-1α (green) staining assay. Cell nuclei were stained with DAPI (blue). Figure 24The results showed that, compared with the other two groups, tumors treated with PTPM under light or no light showed weak green fluorescence after HIF-1α staining, indicating that the PTPM group significantly alleviated tumor hypoxia by catalyzing the production of O2 from endogenous H2O2. However, tumors treated with PET and PTP both showed a strong green signal of HIF-1α, proving that the expression level of HIF-1α was high, indicating severe tumor hypoxia. These phenomena suggest that the MnO2 coating can catalyze the production of O2 from H2O2 in the tumor to alleviate tumor hypoxia, which may help enhance the efficacy of O2-dependent PDT.

[0107] (3) Evaluation of photodynamic therapy effect The stability and high retention rate of PTP coating were confirmed by simulating an acidic tumor environment in vitro, and the in vivo PDT efficiency in KYSE tumor-bearing mice was further evaluated. Specifically, mice were randomly divided into four groups (n=4 per group): 1) PET implantation group (no light exposure), 2) PTP implantation group (660 nm light exposure for 10 min), 3) PTPM implantation group (no light exposure), and 4) PTPM implantation group (660 nm light exposure for 10 min). When the tumor volume reached approximately 150 mm... 3 Different samples were implanted into mice, followed by different treatments. The treatment regimen included light stimulation on days 1, 3, 5, 7, and 9. Figure 25 ).

[0108] Monitor tumor volume during treatment, such as Figure 26 As shown, tumors in the PET and PTPM groups exhibited similar growth trends, growing rapidly within 12 days, demonstrating that PTPM coating has no biotoxicity. At the end of treatment, tumor growth in the PTP plus laser irradiation group was significantly inhibited, with a 30% reduction in tumor volume. In contrast, mice treated with PTPM plus laser irradiation showed significant tumor growth inhibition, with an 80% reduction in tumor volume, higher than the 66.67% reported in existing techniques (Han Q, Zou P, Wei X, et al. An esophageal stent integrated with wireless battery-free movable photodynamic-therapy unit for targeted tumor treatment [J]. Materials TodayBio, 2025, 30: 101394.), indicating that PTPM-coated PDT has a good anti-tumor effect. Figure 26 Furthermore, the tumor weight further confirms the excellent PDT effect of PTPM coating. Figure 26(Right) It can be seen that the tumor mass treated with PTPM plus laser irradiation was reduced by 71.43±3.15% compared with the PET group. During the 12-day treatment period, the PTPM plus laser group showed excellent tumor suppression effect. Combined with the previous data on the 28-day retention rate in vitro (90.63%), it is suggested that extending the treatment cycle may further improve the efficacy.

[0109] The photos taken on day 14 show that PTPM failed to inhibit tumor growth without laser irradiation. In contrast, mice treated with PTPM plus laser irradiation exhibited significant tumor growth inhibition. At the end of treatment, the tumors in the PTPM plus laser irradiation group were significantly smaller than those in the other three groups. Figure 27 ) Furthermore, the tumor tissues extracted from the four groups were subjected to H&E staining, Ki67 immunohistochemical staining, and TUNEL staining to assess the microscopic changes in the tumor tissues, the proliferation capacity of tumor cells, and apoptosis. Figure 28 As shown, H&E staining images revealed significant nucleus shrinkage and increased space between tumor cells in the PTPM plus laser irradiation group, indicating typical necrosis / apoptosis of tumor cells. In contrast, the morphology of tumor cells in mice treated with PET and PTPM showed almost no change, while some cells in the PTP group lost their original morphology. TUNEL is a classic experimental technique for detecting apoptosis (programmed cell death). Results showed almost no green fluorescence in the PET and PTPM groups, while the PTP plus laser group showed a small amount of fluorescence. A significant green fluorescence signal was observed in the TUNEL staining images of tumors in the PTPM plus laser group, demonstrating severe apoptosis. Ki67 expression is closely related to mitosis and is used as an indicator of cell proliferation. Positive cell nuclei appeared brown, with stronger signals in highly proliferating regions. Clearly, the PTPM plus laser group showed downregulated Ki67 expression, indicating strong inhibition of tumor cell proliferation. These experimental results demonstrate that repeated PDT in the PTPM group can effectively trigger tumor cell apoptosis and inhibit its proliferation.

[0110] (4) Safety assessment of tumor treatment The safety of medical devices is a primary concern in the medical field. In vivo safety was evaluated in mice through changes in body weight, histological staining analysis of major organs, and assessment of blood biochemical indicators. Initially, the growth of nude mice was monitored every two days during treatment. Results showed no significant differences in body weight among the four groups of nude mice. Figure 29 This indicates that the implantation of the three groups of membranes did not affect the nutritional metabolism of the mice.

[0111] Histological staining of major organs from the extracted mice was performed to detect any pathological changes. H&E stained sections are shown below. Figure 30As shown, the major organs exhibited standard morphology and structure, indicating that PET, PTP, and PTPM coatings all possess good biocompatibility.

[0112] Serum biochemical markers (ALT, AST, BUN, CREA) analysis is a core method for assessing the impact of drugs or treatments on liver and kidney function. After a 12-day treatment cycle, blood biochemical markers were analyzed in four groups of mice. The results showed no significant differences in biochemical markers among the four groups: the PET implantation group (no light exposure), the PTP implantation group (660 nm light exposure for 30 min), the PTPM implantation group (no light exposure), and the PTPM implantation group (660 nm light exposure for 30 min). Figure 31 This indicates that PTPM effectively treats the KYSE xenograft tumor model while having minimal impact on liver function, kidney function, and other physiological indicators. These results demonstrate that the prepared PTPM exhibits no significant toxicity and good biosafety, making it a promising PDT material for cancer treatment.

[0113] In summary, tumors treated with PTPM-coated stents, compared to those treated with PET and PTP-coated stents, showed a weak green signal of HIF-1α, indicating lower HIF-1α expression levels and suggesting relief of tumor hypoxia, thus enhancing the efficacy of O2-dependent PDT. Tumor volume changes revealed that mice treated with PTPM-coated stents plus laser irradiation exhibited significant tumor growth inhibition, with tumor volume reduced by 80%. Further confirmation through H&E staining, Ki67 immunohistochemical staining, and TUNEL staining further demonstrated that PTPM-coated stents plus laser irradiation promoted tumor apoptosis and inhibited tumor cell proliferation. PTPM implantation does not affect the nutritional metabolism of mice and exhibits good biocompatibility, providing a research direction for the development of next-generation functional esophageal stents.

[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit the solutions. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention based on the understanding of the present invention, without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A photosensitizer-immobilized esophageal stent coating based on a zirconium-based metal-organic framework, characterized in that, The photosensitizer-immobilized esophageal stent coating includes a nitric acid / polyethyleneimine intermediate adhesion layer, a PCN-224NPs photodynamic layer disposed on the intermediate adhesion layer, and a MnO2 smart response channel layer disposed on the photodynamic layer for in-situ reaction to alleviate hypoxia. In the PCN-224 NPs photodynamic layer, Zr ions combine with the phenolic hydroxyl groups of the nitric acid / polyethyleneimine intermediate adhesive layer and are fixed on the surface of the TA / PEI adhesive layer. The PCN-224 NPs photodynamic layer is loaded with a photosensitizer.

2. The photosensitizer-immobilized esophageal stent coating according to claim 1, characterized in that, The photosensitizer is a porphyrin photosensitizer, AlPcS4, Fe-TCPP nMOFs, UCNPs@Porphyrin MOFs, or Cu-MOFs.

3. The photosensitizer-immobilized esophageal stent coating according to claim 1, characterized in that, The photosensitizer-immobilized esophageal stent coating is excited by laser, and the laser conditions are: wavelength 600~1000 nm, irradiation intensity 30~60 mW / cm², and interaction time 5~20 min; preferably, the laser conditions are: wavelength 630 nm, irradiation intensity 50 mW / cm², and interaction time 10 min.

4. The photosensitizer-immobilized esophageal stent coating according to claim 1, characterized in that, The photosensitizer-immobilized esophageal stent coating is a stent morphology placed at the site of the patient's esophageal tumor.

5. The photosensitizer-immobilized esophageal stent coating according to any one of claims 1 to 4, characterized in that, It is prepared by the following method: S1. Preparation of zirconium-based metal-organic framework PCN-224 NPs ZrOCl2·8H2O, benzoic acid solution and TCPP were mixed in a weight ratio of (10~30):(1000~2000):(100~200) and stirred at 80~100℃ for 5~6 h to obtain PCN-224 NPs; S2. Preparation of polyphenol-assisted adhesive layer TA / PEI@PET The PET film of the integrated braided scaffold was immersed in a buffer solution with a concentration of 0.4~0.8 mg / mL TA. After mixing and reacting for 1~4 h, PEI was added to make its concentration 5~20 mg / mL. The pH was adjusted to 7.0~9.

0. After mixing and reacting for 1~4 h, the TA / PEI@PET film was obtained. S3. Fabrication of the scaffold photodynamic layer PCN-224 NPs@TP The TA / PEI@PET film was immersed in a PCN-224 NPs HEPES solution with a concentration of 0.5~2.0 mg / mL to co-deposit the scaffold photodynamic layer PCN-224 NPs@TP; S4. Preparation of the hypoxia relief layer PCN-224 NPs@TP was immersed in a MnCl2 solution with a concentration of 2.5~10.0 mg / mL and reacted at pH 9~10 for 0.1~1 h to obtain a photosensitizer-immobilized esophageal stent coating.

6. The photosensitizer-immobilized esophageal stent coating according to claim 5, characterized in that, The PET coating of the integrated braided bracket is prepared by the following method: NiTi spring yarn and PET yarn are regularly braided, with a braiding angle of 55~58°, a braiding pitch of 3.9~4.7 inches, and an inner diameter of 8~10 mm; the PET coating thickness is 0.46~0.50 mm; the NiTi spring yarn is a spring structure composed of NiTi alloy yarn heated and shaped, with a diameter of 0.1~0.3 mm; the number of NiTi spring yarns is 8~12, and the pitch of the NiTi spring yarn is 1.0~3.0 mm; the PET yarn is a PET multifilament composed of monofilaments with a linear density of 500~1500 D and 144~288 f.

7. The application of the photosensitizer-immobilized esophageal stent coating as described in claim 1 in the preparation of medical devices for tumor treatment.

8. The application according to claim 7, characterized in that, The tumor is esophageal cancer or other stricture tumor lesions.

9. The application according to claim 8, characterized in that, The tumor microenvironment exhibits the following changes: hypoxia, acidic pH changes, and endogenous H2O2 production.

10. A photosensitizer-immobilized esophageal stent, characterized in that, The esophageal stent coating with photosensitizer immobilization as described in any one of claims 1 to 6.